Disaster Knowledge and Household Preparations of Selected Communities in Central Luzon, Philippines: Basis for Enhanced Community Disaster Education Program - Asio, John Mark (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2020)
Disaster is nature’s worst event that can happen anytime and anywhere. It creates unfathomable destruction to everything. This study aimed to analyse and explore the disaster knowledge and household preparations of individuals in selected communities located in Central Luzon, Philippines. The study used a descriptive research design with the survey as the primary data gathering tool. One hundred thirty (130) respondents took part in the survey from two identified communities in Central Luzon using purposive sampling technique. This study also adopted and modified a research instrument which was subjected to validity and reliability test. The researcher subjected the data gathered with the following statistical tools: weighted mean, t-test, ANOVA and Pearson-r with the help of SPSS 20. The study then generated the following findings (1) the respondents were knowledgeable about disasters and the households were prepared in time of a disaster. In addition, there was a significant difference in the disaster knowledge respondents when grouped according to the community. Also, there exists a relationship between the community of the respondents and their disaster knowledge. Furthermore, a moderate and direct relationship also exists between disaster knowledge and household preparations. Based on the findings the researcher provided a suggestion for an enhanced community disaster education program.